2023
DOI: 10.1002/adsc.202300774
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric [4+2]‐Cycloaddition of Anthracene Derivatives via Hydrazone Activation

Beata Łukasik,
Jakub Ossowski,
Sebastian Frankowski
et al.

Abstract: Enantio‐ and diastereoselective dearomative [4+2]‐cycloaddition reaction between N,N‐dimethylhydrazone derived from 9‐anthracenecarbaldehyde and α,β‐unsaturated aldehydes is reported. The developed strategy utilizes HOMO‐rising activation of diene (via hydrazone formation) and aminocatalytic LUMO‐lowering activation of dienophile (via iminium ion formation). High chemical and stereochemical efficiency have been obtained owing to the application of Jørgensen catalyst. Target cycloadducts were subjected to selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…In order to break the inherent aromatic stability of anthracene, activated functional groups are typically required to assemble on the anthracene ring (Fig. 1C ) 64 . For simple anthracene derivatives and diverse reaction partners with similar poor reactivity to be viable and for conversion to occur under mild reaction conditions, the exploitation of photocatalytic systems to input additional chemical energy from photons has been investigated by chemists 65 .…”
Section: Introductionmentioning
confidence: 99%
“…In order to break the inherent aromatic stability of anthracene, activated functional groups are typically required to assemble on the anthracene ring (Fig. 1C ) 64 . For simple anthracene derivatives and diverse reaction partners with similar poor reactivity to be viable and for conversion to occur under mild reaction conditions, the exploitation of photocatalytic systems to input additional chemical energy from photons has been investigated by chemists 65 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we demonstrated that hydrazone activation of (hetero)­aromatic aldehydes constitutes a useful tool for the development of new organocatalytic transformations. It was shown that such a strategy can be efficiently employed in the asymmetric Friedel–Crafts reaction, (3 + 2)-cycloaddition (for the synthesis of 2,3-dihydro-1 H -pyrrolyzines), or asymmetric [4 + 2]-cycloaddition with hydrazone derived from 9-carboxyanthracene, leading to the formation of the biologically relevant dihydro-9,10-ethaneanthracene scaffold …”
mentioning
confidence: 99%
“… 14 16 It was shown that such a strategy can be efficiently employed in the asymmetric Friedel–Crafts reaction, (3 + 2)-cycloaddition (for the synthesis of 2,3-dihydro-1 H -pyrrolyzines), 15 or asymmetric [4 + 2]-cycloaddition with hydrazone derived from 9-carboxyanthracene, leading to the formation of the biologically relevant dihydro-9,10-ethaneanthracene scaffold. 16 …”
mentioning
confidence: 99%